Geschichte des Küstenverlaufs in der Bucht von Cádiz und San Fernando im Holozän - Schulz, Horst; Barragán Mallofret, Daniel; Becker, Veith (Madrider Mitteilungen, 2020)
Deutsche Zusammenfassung folgt.